2021
DOI: 10.1097/iyc.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Knowledge Base, Landscape, and Trends in Leadership Literature in Early Intervention, Early Childhood, and Early Childhood Special Education

Abstract: Effective leadership is regarded as pivotal to the vitality of organizations. In early childhood programs, strong leadership is particularly critical because program leaders are the gatekeepers of quality. However, the fields of early intervention, early childhood, and early childhood special education (EI/EC/ECSE) continue to struggle with the challenges of being overlooked regarding leadership research, potentials, qualities, and abilities. This scoping review aimed to identify and synthesize the available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This may be attributed to the vast healthcare system in the USA and requirements for evidence-based practice that permeates all healthcare professions. In contrast to early intervention and early childhood special education where Movahedazarhouligh 89 reported a paucity of research on leadership research, this topic is well studied in the healthcare profession.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the vast healthcare system in the USA and requirements for evidence-based practice that permeates all healthcare professions. In contrast to early intervention and early childhood special education where Movahedazarhouligh 89 reported a paucity of research on leadership research, this topic is well studied in the healthcare profession.…”
Section: Discussionmentioning
confidence: 99%
“…Navigating their role as EI/ ECSE faculty leaders may include embedding work demands such as integrating teaching, research, and service. It is important for universities to support the building and maintaining of local EI/ECSE leadership to work toward improving outcomes for young children with disabilities and their families, and in doing so, supporting the advancement of EI/ECSE leadership and educational reform (Movahedazarhouligh, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review can be conducted when researchers aim to identify key characteristics or factors related to a concept as well as identify knowledge gaps (Arksey and O’Malley, 2003; Munn et al , 2018). Identified as a type of literature review (Grant and Booth, 2009), scoping reviews have been used broadly in health and medical practice research but have also been used in leadership research related to health care (Malila et al , 2018), school leadership (Tintoré et al , 2022) and early childhood education (Movahedazarhouligh, 2021). To conduct a scoping review, a research or review question is developed, inclusion and exclusion criteria for the literature is created, relevant studies are identified through a defined database search protocol, literature is included or excluded from the review by team members based on inclusion and exclusion criteria, selected literature is charted to extract relevant information from the literature and selected data/literature are analyzed using qualitative thematic analysis, and findings are presented (Arksey and O’Malley, 2003; Levac et al , 2010; Colquhoun et al , 2014).…”
Section: Methodsmentioning
confidence: 99%